GAYA SENI ARCA MASA KᾹḌIRI: STUDI TERHADAP ARCA CANDI GURAH DAN CANDI TONDOWONGSO - Sukawati Susetyo; Ashar Murdihastomo; Agustijanto Indradjaja; Dimas Nugroho (Badan Riset dan Inovasi Nasional, 2021)
In the archaeology Hindu-Buddhist era in Indonesia, there are several known art styles temple building architecture and statue art: Early Classical Era and Late Classical Era. In more detail, that several eras can be described that Early Classical Era developed during the Old Mātaram era with the center of its reign at Central Java, and Late Classical Era Style developed during Kāḍiri/Siŋhasāri and Majapahit with the center of its reign at East Java. Late Classical Era Style divided into two subs, Kāḍiri/Siŋhasāri and Majapahit. Kāḍiri as an early dynasty in East Java not yet known clearly what the special characteristic style of its temple is building architecture and its statue art, and only been told that the Kāḍiri Era Style is the connecting line between Early Classical Era Style and Late Classical Era. This essay intends to find out special characteristics of the Kāḍiri Era Style (transition art style). For this reason, the research was carried out on statues comes from Gurah Temple and Tondowongso Temple, both temples knew the date, with relative dating method or absolute dating method. From this iconographic research in detail will describe parts of the statues, from then will obtain several features that always appear, and that’s characteristics are considered as a strong characteristic from statues from Kāḍiri Era Style. Dalam arkeologi masa Hindu Buddha di Indonesia, dikenal gaya seni arsitektur bangunan candi dan seni arca masa Klasik Tua dan Klasik Muda. Dapat dijabarkan secara lebih rinci bahwa seni Klasik Tua berkembang pada masa Mātaram Kuna dengan pusat pemerintahan di Jawa bagian Tengah, sedangkan Seni Klasik Muda berkembang pada masa Kāḍiri/Siŋhasāri dan Majapahit dengan pusat pemerintahan di Jawa Timur. Seni Klasik Muda terbagi menjadi dua, yaitu Kāḍiri/Siŋhasāri dan Majapahit. Kāḍiri sebagai suatu dinasti awal di Jawa Timur belum diketahui secara jelas apa saja ciri-ciri khusus, seni bangun candi maupun seni arca, dan hanya dikatakan bahwa gaya seni masa Kāḍiri adalah benang merah yang menghubungkan antara gaya seni Klasik Tua dengan gaya seni Klasik Muda. Tulisan ini bertujuan mengetahui ciri-ciri khusus arca-arca masa Kāḍiri (gaya seni peralihan). Untuk itu, perlu dilakukan penelitian terhadap arca-arca yang berasal dari Candi Gurah dan Candi Tondowongso. Kedua candi tersebut sudah diketahui pertanggalannya, baik secara relatif maupun absolut, yaitu dari masa Kāḍiri. Melalui penelitian ikonografi secara mendetil terhadap bagian-bagian arca didapatkan beberapa ciri yang selalu muncul, dan ciri tersebut dianggap sebagai ciri kuat arca-arca masa Kāḍiri.